TIGIT blockade in the context of BCMA-CART cell therapy does not augment efficacy in a multiple myeloma mouse model - Aina Oliver-Caldes; Joan Mañe Pujol; Anthony M. Battram; Lorena Perez-Amill; Mireia Bachiller; Hugo Calderon; Maria Castella; Judit Carpio; Sergi V. Salsench; Natalia Tovar; Oriol Cardus; Alvaro Urbano-Ispizua; et al. (OncoImmunology)
BCMA-directed CAR-T therapies have shown promising results in multiple myeloma (MM). However, patients continue to relapse. T cell exhaustion with increased TIGIT expression is a resistance mechanism which was confirmed in CAR-T cells from ARI0002h trial, an academic CAR-T developed in our institution. We aimed to analyze the impact of blocking TIGIT on the efficacy of ARI0002h. We used three different strategies to block TIGIT: (1) Addition of an external blocking anti-TIGIT-antibody (Ab), (2) Modify ARI0002h into a 4th generation CAR-T, named ARITIGIT, capable of secreting a soluble TIGIT-blocking scFv and (3) TIGIT knock-out in ARI0002h using CRISPR/Cas9. Each strategy was evaluated in vitro and in vivo. Adding a TIGIT-blocking Ab to ARI0002h improved in vitro cytotoxicity, but failed to enhance mice survival. The new 4th generation CAR-T, ARITIGIT, was also unable to achieve better survival outcomes despite favoring the in vivo model by using a myeloma cell line with high expression of the TIGIT ligand PVR. Interestingly, when mice were challenged with a second infusion of tumor cells, mimicking a relapse model, a trend for improved survival with ARITIGIT was observed (p = 0.11). Finally, TIGIT-knock-out on ARI0002h (KO-ARI0002h) using CRISPR/Cas9 showed similar in vitro activity to ARI0002h. In an in vivo stress model, TIGIT KO-ARI0002h prolonged survival (p = 0.02). However, this improvement was not significant compared to ARI0002h (p = 0.07). This study failed to demonstrate a significant benefit of TIGIT-blockade on ARI0002h cells despite using three different approaches, suggesting that targeting a single immune checkpoint may be insufficient.